ANALISIS KINERJA PEGAWAI SEKSI PEMERINTAHAN DI KANTOR CAMAT BATU HAMPAR KABUPATEN ROKAN HILIR - Ario Wandika; Tuti Khairani Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In the government structure the unitery state of Indonesian, the subdistrict regions is equipment of regency city. This case accord with uu 2004 no 32 about the regions government in pasal 27 ayat 2 the region equipments or regency city consists of regions secretariat, DPRD secretariat, department of region and it means that subdistrict is one of regency region equipment the implementer of goverment headed by a camat. In here the roles of subdistrict very imforta district. On the other words this subdistrict would have many deficiencies for facility and human resources.One of organization that serve the people is a subdistrict office of batu hampar, regency of rokan hilir. The camat office is one of organization that have a major role in managing and regulating the people. Any five villages in subdistrict of batu hampar. They are bantayan village, bantayan hilir, sungai sialang,sungai sialang hulu, and bantayan baru.the local regulations in regency of rokan hilir about establishment of the organizational structure, employment, main duties and villages regency government of rokan hilir the third shapter in the part 2 about employment and basic duties pasal 5 ayat 1 : subdistricts is the camat duties as regions equipment regency of rokan hilir. Pasal 5 ayat 2 : camat is implementer to does the goverment mission by bupati to take a care partial autonomy and the pasal 5 ayat 4 : camat position and basic duties.Part 2 about employment and basic duties pasal 6 have the basic duties to help bupati in implement develop governments and living development. The people in subdistrict regions with develation of affair giyen by bupati.Key words :analysis Performance,cervicing, capability.